Advances in macro-bioactive materials enhancing dentin bonding - Junping Fan; Pei Wang; Shen Wang; Rong Li; Yaoxi Yang; Lei Jin; Yingying Sun; Dongfang Li (Discover Nano, 2025)
Abstract The long-term stability of dentin bonding is equally crucial for minimally invasive aesthetic restoration. Although the dentin bonding meets clinical standards at the initial stage, its long-term efficacy remains suboptimal owing to the impact of physiological factors. Herein, we present a comprehensive analysis of macro-bioactive materials, including nanomaterials and polymer materials, to improve the longevity of dentin bonding and extend the lifespan of adhesive prosthetics through various mechanisms to achieve sustained and stable dentin bonding effects over an extended period. On the one hand, the macro-bioactive materials directly inhibit the enzymatic activity of matrix metalloproteinases (MMPs) or impede the acidogenic abilities of cariogenic microorganisms, thereby enhancing the local pH within the oral cavity. On the other hand, they indirectly prevent the activation of MMPs, thereby safeguarding the structural integrity of the resin–dentin bonding interface and efficiently improve its long-term stability. Moreover, these macro-bioactive materials establish cross-links with collagen fibers, promoting bionic remineralization and protecting the exposed collagen fibers within the hybrid layer from degradation. These processes ultimately enhance the mechanical properties of the resin–dentin bonding interface and efficiently improve its long-term stability.